Study of Organic Carbon (OC), and Calcium Carbonate (CaCO3) in the coastal area of Aceh Besar - Sayed Abdul Azis; Muhammad Irham; Sugianto Sugianto (Depik, 2022)
Most of the coastal areas of Aceh Besar are areas of accumulation of organic compounds, one of which is Organic Carbon (OC). The purpose of this study was to analyze the chemical content by looking vertically at the content of OC, soil pH and Calcium Carbonate (CaCO3) on the coast of Aceh Besar District. Analysis of the OC content using the Walkley and Black method, while to analyze the Calcium Carbonate (CaCO3) using the Titrimetric method. Especially for the analysis of soil pH, only use a pH meter. The results showed that each station had different levels of OC and carbonate. Generally, the presence of OC decreases with depth, while the carbonate content varies. Especially for soil pH, the pH is relative to the alkaline state for each depth. The range of OC content for all stations is 0.18 2.48%, Carbonate 5.36 13.27% and pH 6.37-8.73.Keywords:CoastalOrganic CarbonCarbonateSoil pH